UNICA$H (CIPEEX, 2022)
THE DESIRED OBJECTIVE OF THE UNICASH PROJECT IS THE DEVELOPMENT OF A MOBILE APPLICATION THAT WOULD SERVE TO COLLECT POINTS SINCE THE COMPLETION OF UNIVERSITY WORK TO EXCHANGE THEM FOR BONUSES OR UNIVERSITY RESOURCES.THEREFORE, THE METHOD USED TO CARRY OUT THE PROJECT WAS THROUGH THE DIVISION OF THE PROJECT INTO SQUADS, IN WHICH EACH ONE WILL TAKE CARE OF A SECTOR, THIS PROJECT BEING THE REPORTS MODULES, INCLUDING HOME SCREENS AND LOGIN SCREEN.THE GROUP CHOSE TO GO FOR FRONT-END DEVELOPMENT USING REACT NATIVE, POSTGRESQL, AND COUNTING ON THE TESTING AND MONITORING SQUADS, AND ALSO DESIGN DEVELOPMENT.THE RESULTS ACHIEVED SO FAR ARE THE SCREENS FOR THE FRONT-END, AND A FUNCTIONAL LOGIN SCREEN, IN ADDITION TO REQUIREMENTS AND FUNCTIONALITY DOCUMENTS FOR THE APPLICATION.IN THIS WAY, IT CAN BE CONCLUDED THAT THE PROJECT WILL ADD A LOT TO THE CURRICULUM OF THE PARTICIPANTS, IN ADDITION TO PRODUCING A TOOL THAT WILL BENEFIT THE UNIVERSITY AND ITS STUDY ENVIRONMENT. ENCOURAGING EVEN MORE THE PRACTICE AND COMMITMENT TO CARRYING OUT THE ACTIVITIES PASSED ON TO UNIVERSITY STUDENTS.
Keywords: UniCash; Mobile Application; React Native; Squads.